Biological functions and therapeutic potential of CKS2 in human cancer - Lai, Yueliang; Lin, Ye (Frontiers in Oncology, 2024)
The incidence of cancer is increasing worldwide and is the most common cause of death. Identification of novel cancer diagnostic and prognostic biomarkers is important for developing cancer treatment strategies and reducing mortality. Cyclin-dependent kinase subunit 2 (CKS2) is involved in cell cycle and proliferation processes, and based on these processes, CKS2 was identified as a cancer gene. CKS2 is expressed in a variety of tissues in the human body, but its abnormal expression is associated with cancer in a variety of systems. CKS2 is generally elevated in cancer, plays a role in almost all aspects of cancer biology (such as cell proliferation, invasion, metastasis, and drug resistance) through multiple mechanisms regulating certain important genes, and is associated with clinicopathological features of patients. In addition, CKS2 expression patterns are closely related to cancer type, stage and other clinical variables. Therefore, CKS2 is considered as a tool for cancer diagnosis and prognosis and may be a promising tumor biomarker and therapeutic target. This article reviews the biological function, mechanism of action and potential clinical significance of CKS2 in cancer, in order to provide a new theoretical basis for clinical molecular diagnosis, molecular targeted therapy and scientific research of cancer.